Diversifying vegetable production systems for improving the livelihood of resource poor farmers on the East Indian Plateau - Manickam, Ravishankar; Kaur, Devender Pal; Vemula, Anilkumar; Rathore, Abhishek; Unkovich, Murray; Bellotti, William; Kumar, Ashok; Gorai, Bapi; Madhavan Nair, Ramakrishnan (Frontiers in Sustainable Food Systems, 2023)
Failure of the rice crop, or low rice yield has dire consequences for rice-dependent households, including malnutrition for people in the East Indian Plateau region. Crop diversification could reduce the risks of rice production primarily due to vagaries in rainfall and provide cash income which is not generated from subsistence rice. Farmers in Bokaro and West Singhbhum in the State of Jharkhand, and Purulia in West Bengal participated in experiments conducted with different vegetable crops and legumes in the upland and medium uplands where the traditional crop is broadcasted paddy. We explored four different vegetable systems, (i) cucurbits (rainy /kharif) season - June to September), (ii) growing tomatoes in the “off season” (rainy season - July to October), (iii) growing legume crops in rotation with direct sown rice (dry /rabi season)-November to January), and (iv) intercropping beans with maize (rainy season - June to September). The results showed that all the above crop diversification activities proved much better in terms of income to the farmers, return per man day though the input cost was higher and varied with the systems explored. The small-holding farmers or the citizens were involved in the research which enables them to make better decisions in future. This study not only increase crop diversification and influence the farmers to expand the area under non-paddy crop, especially with vegetables but also enables them to look for new future crops when the supply exceeds the demand. The unique finding is the involvement of communities’ results in sustainability in finding the solution for the future problems with limited support from the external agencies, if needed.